Imaging Sensors and Technologies - Gonzalo Pajares Martinsanz (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
This book provides different technologies and procedures related to imaging sensors. Active or passive imaging sensors capture electromagnetic radiation across the whole spectra or acoustic echoes, which, conveniently arranged in images, allow the extraction of useful information. Researchers, engineers and industry professionals can find the most advanced imaging technologies and developments, together with dedicated image processing and computer vision-based approaches. This book provides insights into and solutions for different problems, covering a broad spectrum of possibilities, thanks to a set of applications and solutions, including 3D data recovery; multispectral analysis; biometrics applications; computed tomography; surface defects; indoor/outdoor systems; surveillance. Advanced imaging technologies and specific sensors are also described on the electromagnetic spectrum (ultraviolet, visible, infrared), including airborne calibration systems; selective change driven, multi-spectral systems; specific electronic devices (CMOS, CCDs, CZT, X-Ray, and fluorescence); multi-camera systems; line sensors arrays; video systems. Some technologies based on acoustic imaging are also provided: acoustic planar arrays of MEMS or linear arrays.